2021
DOI: 10.1051/swsc/2020072
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the Parker spiral with the Reverse In situ data and MHD APproach – RIMAP

Abstract: The reconstruction of plasma parameters in the interplanetary medium is very important to understand the interplanetary propagation of solar eruptions and for Space Weather application purposes. Because only a few spacecraft are measuring in situ these parameters, reconstructions are currently performed by running complex numerical Magneto-hydrodynamic (MHD) simulations starting from remote sensing observations of the Sun. Current models apply full 3D MHD simulations of the corona or extrapolations of photosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 96 publications
0
18
0
Order By: Relevance
“…The background condition of the interplanetary Parker spiral for the ICME simulation is reconstructed by RIMAP using plasma parameters measured by Wind in 2009 between March 3 and March 29 (Biondo et al 2021), around the minimum of solar activity cycle 23. Even if this time frame was chosen due to its relatively calm solar wind conditions, the RIMAP-reconstructed Parker spiral is highly structured in its longitudinal variability (Fig.…”
Section: Model Resultsmentioning
confidence: 99%
“…The background condition of the interplanetary Parker spiral for the ICME simulation is reconstructed by RIMAP using plasma parameters measured by Wind in 2009 between March 3 and March 29 (Biondo et al 2021), around the minimum of solar activity cycle 23. Even if this time frame was chosen due to its relatively calm solar wind conditions, the RIMAP-reconstructed Parker spiral is highly structured in its longitudinal variability (Fig.…”
Section: Model Resultsmentioning
confidence: 99%
“…The additional UV channel correction steps, such as the correction of the spatial response disuniformity, were performed according to Andretta et al (2021). RIMAP (Biondo et al 2021a) is a technique for reconstructing the Parker spiral on the equatorial plane, starting from an analytically built inner boundary and propagating it outwards by solving the time-dependent magnetohydrodynamics (MHD) equations in a frame corotating with the solar equator. This approach was shown to reproduce the fine longitudinal structure of the spiral and to accurately match the features mea-sured at 1 AU.…”
Section: Data and Modelmentioning
confidence: 99%
“…All these previous works made various assumptions to reconstruct the path followed by the solar plasma propagating from the inner corona to the interplanetary medium. The goal of the present work is to accurately reconstruct the Parker spiral and to connect the coronal features observed remotely by the Metis coronagraph (Antonucci et al 2020) on board Solar Orbiter with those detected in situ by PSP, at the time of the first PSP-Solar Orbiter quadrature which occurred on January 2021 , by using the Reverse In-situ and Magnetohydrodynamics APproach (RIMAP, Biondo et al 2021a), a hybrid analytical-numerical method for reconstructing the Parker spiral.…”
Section: Introductionmentioning
confidence: 99%
“…For space weather applications (see, e.g. Biondo, Ruggero et al 2021, relating the properties of the solar wind in situ with the remotely observed structure of the solar corona, by tracing the stream-line in co-rotating frame from the observation point toward its origin site) this is a large difference, meaning that field line associated phenomena (like SEP events) will arrive to Earth some 15 hours later than predicted by Parker (1958) spiral connectivity models. It is important, therefore, that our computational model fully incorporates all principles and opportunities of the earlier models.…”
Section: Stream Aligned Mhd In a Rotating Frame Of Referencementioning
confidence: 99%